The Android – Based Nearby Location App For Orphanage Searches Using Google Place API Technology With Agile System Development Method - Setiadi Sutedja; Edy Edy (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2021)
At this time the public is already aware of the value of sharing with the needy, so the search for orphanages is increasing drastically. Similarly, the use of maps on smartphones is increasing because people are aware of technology and use it in every day. But often people are troubled to know the location of the orphanage in around, as well as the condition of the orphanage which includes the number of children, the number of caretakers, and what are the needs of the orphanage without coming to the location of the orphanage. In addition, there are often overlapping scheduling problems that often make people who want to hold activities experience unilateral cancellation and there is also the issue of donations where people are confused how to give a little from their income to the orphanage without having to come to the location. With agile development systems method designed nearby location application using Google place, which is obtained the core of the problem is the difficulty of finding information orphanages and not easy to find orphanages around. Therefore, with this nearby location application is expected to help the public to find information on orphanages closest to their location, as well as be able to schedule activities that can be monitored in real time. So there is no overlap back on the activity. In addition, there is a function of giving donations, so that people can donate without having to come to the orphanage.